Estimating temperature effects on Drosophila suzukii life cycle parameters. (20th March 2021) - Winkler, Alicia; Jung, Jeanette; Kleinhenz, Benno; Racca, Paolo
Abstract : Drosophila suzukii is an invasive, polyphagous pest of soft‐skinned fruits, having huge impact on fruit production in Asia, North and South America and Europe including Germany. To investigate the effect of temperature on oviposition, egg‐to‐adult development success and duration, as well as immature heat survival and adult cold survival for a German D. suzukii population several experiments were conducted under different constant temperatures in the laboratory. The resulting life cycle data were described mathematically as functions of temperature and compared with experimental results of other researchers in a summary table. Curve fittings used herein revealed that minimum, optimum and maximum temperatures are: 13.2, 26.7 and 33.6 °C for oviposition, 14.1, 22.6 and 30.0 °C for egg‐to‐adult development success, and 9.6, 27.3 and 35.7 °C for egg‐to‐adult development duration. Eggs and larvae of D. suzukii showed a reduced heat survival within the tested temperature range of 29 to 41 °C and exposure durations from 1 to 8 h. A cold survival rate of 50% was measured at e.g. −6 °C for 4 h in summer morph adults and at e.g. −6 °C for 45 h in winter morph adults confirming that the latter are more cold tolerant. Results obtained in this study for a German population of D. suzukii are similar to those obtained for populations of other origins such as Canada, Japan, Spain and USA. Thus, presumably, present data based on a German D. suzukii population can be used for a new or fine‐tune of already existing population dynamics models of D. suzukii in order to support an effective pest management strategy. Abstract : We investigated the effect of temperature on Drosophila suzukii life cycle. Data were described mathematically as functions of temperature and compared with experimental results of other researchers. We assume that results presented herein can be used to fill gaps in data sets obtained with D. suzukii populations of other geographic origins and vice versa . Thus, the present data can be used for a new or fine‐tune of already existing population dynamics models of D. suzukii in order to support an effective pest management strategy.